The relationship of workplace spirituality, organizational commitment on employees performance, and job satisfaction as moderating variable - Robbie, Iqbal; Roz, Kenny (Technium Social Sciences Journal, 2021)
An organization is a social system that includes a complex set of human interactions with the surrounding community, as well as their relationships with one another and with the outside world. If the climate or workplace conditions support the organization's internal integration process, it will function smoothly. All of these components interact in the system to make it work well. The purpose of this study is to see how the relationship between workplace spirituality and organizational commitment to employee performance is influenced by job satisfaction as a moderating variable of workplace spirituality's impact on employee performance. Questionnaires and in-depth interviews were used to collect data from 177 employees of Islamic banks in East Java Province. The Smart PLS analysis tool is used to process the collected data. The study's findings show that workplace spirituality has a positive and significant impact on employee performance, organizational commitment has no impact on performance, and employee contentment can be moderated by enhancing the impact of workplace spirituality on employee performance